GENERAL AND SPECIFIC FEATURES OF THE GEOGRAPHICAL LOCATION OF THE OKCHADARYA BASIN AND THE LOWER ZARAFSHAN VALLEY - Usmanova, I.I. (ILIM hám JÁMIYET, 2025)
This article examines the geographical location, natural conditions, and historical-geological processes of the Okchadarya Basin and the Lower Zarafshan Valley. The study analyzes the paleogeographic formation, climate changes, and anthropogenic impacts within the Turan Lowland.